Compact Crescent Slot MIMO Antenna With Quad Bands And High Isolation For LTE And 5G Communications - Mohammed Ibrahim, Ayman; Mohd Ibrahim, Imran; Shairi, Noor Azwan (Wydawnictwo SIGMA-NOT, 2020)
A new small crescent MIMO antenna with dimensions of the antenna 31 × 31 × 0.8 mm within the bands of (2.5-2.7, 3.6-4.2, 4.4-4.5, and 5.15-5.6) GHz was designed, and the fabrication and measurement outcomes derived from the use of the MIMO prototype revealed that the crescent MIMO antenna. The small and simple crescent antenna demonstrated high isolation of less than -13.5, -10.5, -15.5 and -29.5dB and envelope correlation coefficient less than 0.01, 0.0024, 0.0008 and 0.0011 respectively. These attributes are suitable for LTE and 5G communications, which is being introduced into China and Japanese markets.